Differences for managing mother's own milk for very preterm infants across 11 European countries. (30th September 2020) - Rodrigues, C; Zeitlin, J; Wilson, E; Toome, L; Cuttini, M; Maier, R F; Pierrat, V; Barros, H
Abstract: Background: There is an ongoing debate about the best practices to handle mother's own milk (MOM) for infants born very preterm (VPT, ≤32 weeks of gestation), specifically to prevent the human cytomegalovirus (HCMV) transmission and bacterial contamination of expressed MOM. Thus, we aimed to compare practices for managing MOM for VPT infants in European neonatal intensive care units (NICUs). Methods: Data were collected as part of the EPICE (Effective Perinatal Intensive Care in Europe) study which explored the use of evidence-based practices for the care of VPT infants in 11 European countries. Structured questionnaires were sent to the head of all participating NICUs with at least 10 VPT admissions. Of the eligible 135 NICUs, 134 replied. Results: A written protocol for breastfeeding/human milk use was available in 91% of the NICUs. Overall, 34% used human bank milk for all VPT infants whose mothers did not express and 56% reported using fresh MOM without restrictions regarding minimum gestational age, birth weight or risk of HCMV transmission (country range: 0-100%). In 22% of units all VPT infants received MOM pasteurized (country range: 0-73%). HCMV serology on all mothers who express their milk was not required in 71% of units (country range: 7-100%). Among NICUs that performed HCMV serology, 3% provided untreated fresh MOM and 23.5% formula in the case of positive mothers. Systematic bacteriological analyses of MOM were not performed in 76% NICUs (country range: 29-100%) while less than 10% did it for the first milk feeding, 7% every week and 8% with another frequency. Conclusions: There are large variations in managing MOM across countries, which could reflect differences in regulations or guidelines, and among the same country NICUs, revealing that different options can operate locally. This variability suggests substantial differences in attitudes about what constitutes best practices among European neonatologists. Key messages: We found significant differences across and within European countries for managing MOM for VPT infants suggesting lack of strong recommendations at the international and national level. There is wide variation in what European neonatologists consider best practices. To guide practice and not jeopardise VPT infants from MOM we need strong evidence-based data.